Continuous (hydro-)dechlorination of aromatic chloride compounds in benzyltoluene - Mitländer, Kerstin; Henseler, J.; Rullo, F.; Nathrath, Phillip; Geißelbrecht, M.; Wasserscheid, Peter; Schühle, Patrick (International Journal of Hydrogen Energy, 2025)
Benzyltoluene is an attractive liquid organic hydrogen carrier (LOHC) compound but needs to be purified after its technical synthesis to remove chloride impurities that would harm the Pt-based hydrogenation and dehydrogenation catalysts used for the reversible LOHC loading and unloading with hydrogen. For this purpose the dechlorination of chlorobenzyltoluene in a benzyltoluene matrix was studied in a continuously operated trickle bed reactor using a commercially available nickel catalyst. The results indicate that the removal of chlorobenzyltoluene is mainly adsorption based. Rapid aging experiments with purposely added chloroaromatic compounds (chlorobenzene and chloronaphthalene) in quantities of up to 9000 ppm suggest that high chloroaromatic loadings lead to reduced dechlorination activity due to a rapid blocking of active sites. The dechlorination capacity per gram of the used catalyst material was determined to be in the range of 2 kg of technical benzyltoluene.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Benzyltoluene; Chloroaromatics; Chlorobenzene; Dechlorination; LOHC